High performance controllers for real-time industrial applications - Chan, John Chok You. (2008)
In this report, discrete time quasi-sliding mode control is presented. Two robust discrete time quasi-sliding mode controllers are proposed for uncertain plants. They are based on the state space and the input-output models. Stability conditions are also given.